The Importance of Technology to the View of the Qur'an for Studying Natural Sciences - Leli; Sunarya, Po Abas; Lutfiani, Ninda; Lestari Santoso, Nuke Puji; Ajeng Toyibah, Restu (Pandawan, 2021)
Islam advances its people to spread science and technology. According to Muslims who believe in the Koran, learning to develop science and technology is an attribute of their faith. Those who are knowledgeable have clearly been shown that they will attain invaluable rewards in the last day. In view of the present current science that can be seen from the unprecedented investment particularly for the characteristic, physical and clinical sciences to expand the considerable advancement in people. In science that depends on the administration of logical, experimental or skeptic perceptions to get ready comprehensive and manageable answers for worldwide ecological science, financial matters and basic individuals have genuinely vanished. This initial attempt to use the restless Westerners was according to the philosophers' view of reunifying science and the ethics of science from a spiritual worldview. We acknowledge that if scholars, organizational technology, technologists, creative and scientific institutions always pay attention to natural events from positivism, naturalist, modernist, empirical, agnostic or theistic philosophical assumptions that describe different branches from secular views to modern science will continue to participate critically. modern cemetery. As strict individuals, we change the viewpoint of the real world, nature and life dependent on the regulation of Tauhid (assertion of indisputably the unity of God as Creator, Ruler and Sustainer of such exists). Such world information is the Qur'an which is articulated like an elective information on the mainstream world, subsequently, It is the ideal opportunity for earnest researchers and goal logical sentiment, particularly youthful science understudies and Muslim researchers, to do the worldview change that is so required in the investigation of regular wonders. We perceive that the unmistakable goal to human advancement and the planetary emergency lies in the reshaping of the Tawheed idea of the Cosmos, Nature and Man as the mystical establishment of the normal sciences.